Business demography and economic growth: similarities and disparities in 10 European Union countries - Andrei, Jean Vasile; Chivu, Luminita; Gogonea, Rodica-Manuela; Iacob, Silvia Elena; Patrascu, Aurelia; Popescu, Constanta; Vasic, Mile; Zaharia, Marian (Journal of Business Economics and Management, 2021)
The main research aim is to investigate and test the long-term existence of a balanced relationship (cointegration) between business demographics and economic growth, expressed in terms of real GDP per capita, and to estimate the econometric models expressing relationships between analyzed variables in European economy. Our The study has focused on ten out of the eleven former communist countries, currently members of the European Union, during the 2006–2016 time period. Croatia was left out due to the shortness of the time series available for it, that the study would have required. These findings have significant implications in designing and shaping the future business models in European former communist countries, and increase convergence. The results obtained confirm the existence of long-term balanced relationships between the variables examined, the forms of which however vary from one cluster of states to another.